Multiple Brain Abscesses of an Acute Lymphoblastic Leukemia Patient Treated by Empiric Antibiotic Treatment - Hidayetoğlu, Erdal Kurtoğlu Taha (Fırat University, 2004)
Objective: One of the infections seen in neutropenic patients is brain abscess. Bacterias (Enterobacteriaceae, Nocardia), fungi and protozoa (toksoplazma) are the common etiologic agents. Mortality is extremely high in spite of antimicrobial therapy. So we intended to present an acute lenfoblastic leukemia patient with brain abscess. Case: Twenty-seven years old female with acute lymphoblastic leukemia suddenly developed fever, headache, nausea, vomiting and sensorymotor loss on the right side of her face on the 27th day of chemotherapy. Combination of cefepime + amikacin + fluconazole + metronidazole was started after the detection of multiple lesions of brain abscess by magnetic resonans imaging (MRI). Vancomycin was added to the combination on the 3rd day since fever was still high and clinical signs and symptoms persisted. On the 3rd day of new combination flucanazole was discarded and liposomal amphotericin B was added instead. On the 2nd day of liposomal amphotericin B fever and neurological signs and symptoms disappeared. Control MRI revealed no abscess lesions. Conclusion: We presented this case since brain abscess has a high mortality rate in neutropenic patients and it was treated successfully by ampirical antimicrobial approach.

Amaç: İmmünsüprese hastalarda görülen en önemli infeksiyonlardan biri de beyin apsesidir. Etiyolojik ajanlar arasında başlıcaları bakteriler (enterobakteriler, nokardia), funguslar ve protozoonlar (toksoplazma) sayılabilir. Çoğu zaman uygulanan antimikrobiyal tedaviye rağmen mortalite yüksektir. Bu nedenle, beyin apsesi antimikrobiyal tedavi ile iyileşen akut lenfoblastik lösemi hastayı sunmayı amaçladık. Olgu: Akut lenfoblastik lösemi tanısı konulan hastada kemoterapinin 27. gününde ani gelişen ateş, başağrısı, kusma, bulantı ve yüzün sağ yarısında sensorimotor kayıp gelişti. Magnetik rezonans (MR) görüntülemesinde multipl beyin apsesi saptanan hastaya sefepim, amikasin, flukanazol ve metronidazol kombinasyonu başlandı. Üçüncü günde ateşi düşmeyen ve klinik düzelme saptanmayan hastanın tedavisine vankomisin eklendi. Bu kombinasyon tedavisinin 3. gününde de düzelme saptanamayan hastanın tedavisinden flukanazol çıkarılarak yerine liposomal amfoterisin B eklendi. İkinci günde hastanın ateşi düşerken nörolojik bulguları kayboldu. Kontrol MR' da apse odaklarının tümüyle kaybolduğu saptandı. Sonuç: Olgumuz mortalitesi oldukça yüksek olan beyin apsesinin ampirik yaklaşımla başarı ile tedavi edilmiş olduğu için sunulmuştur.
Akut Lenfoblastik Lösemili Hastada Gelişen ve Ampirik Yaklaşımla Tedavi Edilen Multipl Odaklı Beyin Apsesi Olgusu